2021
DOI: 10.1002/art.41683
|View full text |Cite
|
Sign up to set email alerts
|

American College of Rheumatology, American Academy of Dermatology, Rheumatologic Dermatology Society, and American Academy of Ophthalmology 2020 Joint Statement on Hydroxychloroquine Use With Respect to Retinal Toxicity

Abstract: Four major medical societies involved with hydroxychloroquine (HCQ) therapy concur on the need for common principles and cooperation to minimize the risk of ocular toxicity. At a daily dosage of ≤5 mg/kg/day actual body weight, the risk of retinal toxicity from HCQ is <2% for usage up to 10 years. Widespread adoption of more sensitive testing techniques, such as optical coherence tomography and automated visual fields, by eye care providers will allow the detection of early toxicity and thus preserve the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 12 publications
1
76
0
4
Order By: Relevance
“…One criticism of these guidelines has been that they do not take into account the clinical nuances of treating patients with SLE ( 8 ), RA, and other rheumatic diseases. That said, a recent multispecialty joint statement (including six rheumatologists) expressed support of the 2016 AAO guidelines while still emphasizing the medication’s importance ( 9 ). Adherence with the AAO guidelines could certainly have unintended consequences, including increased disease activity and loss of other potential benefits from HCQ, including reduced mortality ( 10 ), reduced risk of thrombosis, and reduced metabolic and cardiovascular disease ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…One criticism of these guidelines has been that they do not take into account the clinical nuances of treating patients with SLE ( 8 ), RA, and other rheumatic diseases. That said, a recent multispecialty joint statement (including six rheumatologists) expressed support of the 2016 AAO guidelines while still emphasizing the medication’s importance ( 9 ). Adherence with the AAO guidelines could certainly have unintended consequences, including increased disease activity and loss of other potential benefits from HCQ, including reduced mortality ( 10 ), reduced risk of thrombosis, and reduced metabolic and cardiovascular disease ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of retinopathy at an early stage, before any retinal pigment epithelium loss, is essential to prevent loss of visual acuity. The latest recommendations suggest initial screening in the first year of treatment but can be done within 5 years [56][57][58]. This first screening must determine the existence of previous retinal lesions.…”
Section: Screeningmentioning
confidence: 99%
“…They indicated that there is a critical lack of data from a population-based prospective study on HCQ retinal toxicity. 31 A prospective study to better estimate the risk, risk factors and clinical course of HCQ retinal toxicity is therefore needed.…”
Section: Introductionmentioning
confidence: 99%